Penerapan Strategi PAKEM untuk Meningkatkan Akhlaqul Karimah Santri di TPQ Al-Mubarok Adikarso Kebumen - Khusnul, Mohammad; Fatimah, Siti; Irodati, Fibriyan; Murtajib, Ahmad (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Improving students' moral character is a primary focus of learning at the TPQ (Islamic Junior High School). This study aims to improve students' moral character through the implementation of the PAKEM (Active, Creative, Effective, and Enjoyable Learning) strategy at the Al-Mubarok Adikarso TPQ in Kebumen. The method used was Classroom Action Research (CAR), implemented in two cycles. Each cycle included planning, implementation, observation, and reflection. The subjects were students at the TPQ Al-Mubarok Adikarso Kebumen, volume 3. Data collection techniques used observation, interviews, and documentation, while data analysis used the Miles and Huberman model. The results showed an increase in students' positive behaviors, such as honesty, discipline, politeness, and responsibility after the implementation of the PAKEM strategy. This approach was able to create a more enjoyable learning atmosphere and encourage students' active involvement in the learning process. In conclusion, the PAKEM strategy is effective in improving students' moral character in the TPQ environment.Peningkatan akhlaqul karimah santri menjadi fokus utama dalam pembelajaran di TPQ. Penelitian ini bertujuan untuk meningkatkan akhlaqul karimah santri melalui penerapan strategi PAKEM (Pembelajaran Aktif, Kreatif, Efektif, dan Menyenangkan) di TPQ Al-Mubarok Adikarso, Kebumen. Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus. Setiap siklus meliputi perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah santri TPQ Al-Mubarok Adikarso Kebumen jilid 3. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi, sedangkan teknik analisis data menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan adanya peningkatan perilaku positif santri, seperti jujur, disiplin, sopan santun, dan tanggung jawab setelah diterapkannya strategi PAKEM. Pendekatan ini mampu menciptakan suasana belajar yang lebih menyenangkan dan mendorong keterlibatan aktif santri dalam proses pembelajaran. Kesimpulannya, strategi PAKEM efektif dalam meningkatkan akhlaqul karimah santri di lingkungan TPQ.